Linguistics for business (L4B) der Universität Łódź: ein Studiengang im Geist der Kompetenz- und Praxisorientiertheit. Sprachenbarometer Łódź 2021 – Stand und Prognosen - Stawikowska-Marcinkowska, Agnieszka (2022)
The university's relations with the social and economic environment are becoming an increasingly important aspect of higher education, in addition to the university's traditional missions. In addition to education and research, the so-called third mission of the university is developing, which includes relations with the business sector, the public sector and the non-governmental sector, i.e. the socio-economic environment. The goal of the University's cooperation with employers is to share experiences and strengthen cooperation with entrepreneurs and employers. The latter can co-design teaching programs, conduct courses and workshops, organize internships or present their own solutions to various research problems. Therefore, the aim of this paper is to show the role and importance of foreign and specialized language teaching in the context of interdisciplinary studies oriented to the needs of the labour market. This is promoted by the study conducted within the framework of the project Language Barometer Łódź 2021.
Keywords: linguistics for business; languages for specific purposes; business services; professional communication; labour market